Effects of nutrient levels on pen-raised ring-necked pheasant performance and feather growth parameters. - Delfelder, Christopher James (Kansas State University, 2021)
As more upland gamebird habitat is cleared for residential housing and commercial agriculture operations, the industry for restocking and hunting commercially produced ring-necked pheasants has grown substantially. While most commercial poultry production involving broilers and turkeys are evaluated by feed consumption and body growth parameters such as meat yield, the commercial pheasant production industry puts more value on a leaner bird with good feather quality. Feather quality may consist of the overall color of feathers and consistency of feather growth, as well as length of tail feathers in male pheasants raised for release. Three research experiments were conducted to evaluate the effects of different nutrient levels and their effects on general body parameters as well as how those values affected certain feather growth characteristics. The first experiment was conducted to evaluate the effects of graded levels of protein on male pheasant chick performance and tail feather length in the 3- to 6-week and 6- to 9-week growth periods. The results of this experiment indicated that pheasant chick performance was affected based on starter ration protein levels (P<0.05) but the tail feathers of the male pheasant chicks were not affected by the addition or subtraction of protein into the diet (P>0.10). The next trial was conducted to evaluate the effects of graded protein and lysine levels in the starter phase on female pheasant chicks performance from 0 to 4 weeks of age and then subsequently measured for compensatory growth during the 4- to 8-week growth period. The data shows that hen pheasant chick performance was affected by starter ration protein and lysine levels during the first 4 weeks of growth (P<0.05) but body weight and feed conversion ratio were not significantly affected during the second feed period (P>0.10). The final experiment measured graded levels of methionine in the diets and their effects on growth performance parameters as well as feather quality of male ring-necked pheasants at 24 weeks of age. The growth parameter data showed that the males fed higher levels of methionine exhibited a greater effect on body growth characteristics as well as positive growth on feather quality at a young age. In conclusion, certain body growth parameters and feather quality characteristics in ring-necked pheasants can be greatly affected by different nutrient levels in the diet. Through proper management of these differences, birds raised in different climates and seasons can be managed with proper phase feeding and feed costs may be significantly decreased.
Keywords: Reduced protein; Feather quality; Supplemental amino acids; Compensatory growthRing-necked pheasant